Weight Threshold Check Coding for Dimmable Indoor Visible Light Communication Systems - Yu Zuo; Jian Zhang; Yan-Yu Zhang; Ru-Han Chen (IEEE Photonics Journal)
To provide energy savings and ecological benefits, dimming control is a crucial factor in indoor visible light communication (VLC) system where desired brightness levels can be achieved. General dimming control methods have an adverse effect on communication, e.g., limiting the achievable data rate or degrading the error performance. In this paper, we propose a code-based method weight threshold check code (WTCC), which can achieve dimming control as well as improve spectral efficiency further. Moreover, the proposed WTCC has a low implementation complexity with a simple encoding/decoding structure. Finally, simulations have been carried out in terms of normalized power requirement, spectral efficiency, and error performance, which prove WTCC can provide a balance between the two basic functions of VLC: illumination and communication.